Efecto Tequila : sistema bancario y su solidéz - Day, Jorge; Reyes, Gustavo (Universidad Nacional de Cuyo. Facultad de Ciencias Económicas, 1997)
Fil: Day, Jorge. Universidad Nacional de Cuyo. Facultad de Ciencias Económicas